O conjunto habitacional das "Torres Vermelhas" da Pasteleira. - Ana Rita dos Santos Pimenta (2013)
#e study presented herein, focuses on public housing and the social 'projects' and developments in the city of Porto, in the second half of the twenteeth century. #e analysis and interpretation of the features, context and in"uence of the age in which this counstruction is set, are indeed the main objectives of this research. #e cornerstone of this study is the "Torres Vermelhas" compound in the Pasteleira neighbourhood, designed in 1966, with construction beginning in 1972. #e choosing of this compound is closely related with the diversity and complexity of themes that arise from its thorough study. Its setting, in a fractioned urban planning, amongst various on-going interventions and the concerning need to relate its construction with varying surroundings, shaped by opposing ages and socio-economic features, whilst never disregarding the purpose for which it was conceived, creating a close comparison with other recurring cases of modern arquitectural development in the city of Porto. Furthermore, the formal features of the structure are also important in the sense that this relancou a new perspective on building typology for social housing, in line with the appearance of modern principles during the twentieth century, especially in the sixties, amid resistance which arose from criticisms to previous modernist endeavours. #e particular feature of this housing project, especially compared with other contemporary interventions, highlights the "experimentalism" that modernist production yielded in the development of "new" settlements in the city and accordingly, in the city's outlines, bearing in mind it was being built at the same time as other construction projects in Portugal. Referencing and framing the emergence of low-income social housing in Porto, will provide a revisit on previously used models, and sets the foundations to better understand that "new age" arquitects should develop a renewed outlook and approach.